2011
DOI: 10.1021/nn1031998
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrophobicity on the Surface-Catalyzed Assembly of the Islet Amyloid Polypeptide

Abstract: The islet amyloid polypeptide (IAPP) is a hormonal factor secreted by the β-cells in the pancreas. Aggregation of misfolded IAPP molecules and subsequent assembly of amyloid nanofibrils are critical for the development of type 2 diabetes mellitus. In the physiological environment, amyloid aggregation is affected by the presence of interfaces such as cell membranes. The physicochemical properties of the interface dictates the interaction of the peptide with the surface, i.e., electrostatic and hydrophobic inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
85
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 42 publications
8
85
2
Order By: Relevance
“…The AFM images of these aggregates showed that they were composed of lined-up oligomers. Formation of similar fibers by the islet amyloid polypeptide, related to type 2 diabetes, has been recently reported (46). The fibrous aggregates formed in an acidic solution are reminiscent of the amyloid plaques that are observed in histopathology of brain tissues from Alzheimer patients (36,47).…”
Section: Discussionmentioning
confidence: 89%
“…The AFM images of these aggregates showed that they were composed of lined-up oligomers. Formation of similar fibers by the islet amyloid polypeptide, related to type 2 diabetes, has been recently reported (46). The fibrous aggregates formed in an acidic solution are reminiscent of the amyloid plaques that are observed in histopathology of brain tissues from Alzheimer patients (36,47).…”
Section: Discussionmentioning
confidence: 89%
“…Alternatively, formation of non-fibrillar species has been observed in both IAPP and Aβ amyloidogenesis when monomers interact with hydrophobic surfaces 22, 23 . This suggests that IAPP-aLac could act as a seed, promoting contact between monomeric or low-order oligomeric IAPP species, yet directing aggregation off-pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Fourth, the technique works well for studying the interaction between peptide aggregation and other biomolecules in the cellular milieu, such as membranes (49)(50)(51)(52)(53)(54) and other lipid structures (22,55,56). Finally, these coarse-grained simulations are ideal to study systems that use a solid surface as a substrate on which aggregates adsorb, a setup common in many experiments (e.g., atomic force microscopy) (57)(58)(59)(60)(61)(62)(63)(64).…”
Section: Coarse-grained Modelsmentioning
confidence: 99%